Teaching sport concepts and skills : a tactical games approach for ages 7 to 18 - Mitchell, Stephen A.; Oslin, Judith L.; Griffin, Linda L. (Champaign, IL : Human Kinetics, 2013)
This third edition now covers all school age groups from primary to secondary. It shows teachers how to make the switch from using a traditional games teaching approach to a tactical one using detailed unit and lesson plans, a DVD-ROM with video clips, reproducible elements and a standards-linked performance assessment system.
With DVD
Includes bibliographical references (p. 655 - 657).
Keywords: Sports; Coaching (Athletics)